Left atrial isomerism - sonographic signs at 12 weeks - Pires,Rafaela (2022)
Abstract Left atrial isomerism is a rare syndrome responsible for multiple cardiac, visceral and vascular malformations. Due to its high phenotype variability, prognosis can be poor. This report aims to share some unusual ultrasonographic findings of an affected fetus at 12 weeks of gestation. The discrepancy between atrial and ventricular rates hinted towards the assessment of this disorder, at such an early stage. Ultrasonographic superb microvascular imaging technique corroborated the diagnosis. This case highlights the importance of a thorough morphological evaluation at the first trimester scan.